Clinical features and management of equine post operative ileus (POI): Survey of Diplomates of the American Colleges of Veterinary Internal Medicine (ACVIM), Veterinary Surgeons (ACVS) and Veterinary Emergency and Critical Care (ACVECC). (1st December 2015) - Lefebvre, D.; Hudson, N. P. H.; Elce, Y. A.; Blikslager, A.; Divers, T. J.; Handel, I. G.; Tremaine, W. H.; Pirie, R. S.
Summary: Reasons for performing study: A recent survey of European Colleges (European College of Equine Internal Medicine [ECEIM] and European College of Veterinary Surgeons [ECVS]) revealed the different strategies implemented by, and some of the challenges facing, European clinicians presented with cases of post operative ileus (POI). It was concluded that further comparative analysis of opinions, canvassed from additional colleges of equine veterinary specialism worldwide, would provide valuable additional insight into current POI knowledge on a more global scale. Objectives: To report and compare the current strategies favoured by American veterinary specialists when managing POI in horses that underwent emergency colic surgery. Study design: Cross‐sectional survey. Methods: Electronic invitations were sent to 814 Large Animal specialists, including 3 colleges: the American College of Veterinary Internal Medicine (ACVIM), American College of Veterinary Surgeons (ACVS) and the American College of Veterinary Emergency and Critical Care (ACVECC). Results: The response rate was 14% (115/814). The majority of respondents (68%) reported an estimated prevalence range of POI of 0–20%. The presence of reflux on nasogastric intubation was the main criterion used to define POI. A lesion involving the small intestine was considered the main risk factor for POI. Anti‐inflammatory drugs, intravenous (i.v.) fluids and antimicrobial drugs were the primary strategies used when managing POI. Flunixin meglumine and i.v. lidocaine were the drugs most commonly used in the treatment of horses with POI. Supplementary management strategies targeted mainly the prevention of post operative adhesions, infection and inflammation. Conclusions: There is a lack of consensus on the clinical definition of POI. Prospective and objective clinical assessment of the effectiveness of the different strategies contained within this and the European survey is necessary in order to identify a standardised approach to the management of equine POI.